A Prospective Randomized Trial Comparing 2 Different Paclitaxel-Coated Balloons in De Novo Coronary Artery Disease - Eun-Seok Shin, MD, PhD; Yongwhi Park, MD, PhD; Jong-Young Lee, MD, PhD; Ae-Young Her, MD, PhD; Min-Ku Chon, MD, PhD; Sunwon Kim, MD, PhD; Seung-Woon Rha, MD, PhD; Gyu Chul Oh, MD, PhD; Deok-Kyu Cho, MD, PhD; Bitna Kim, MS; Jang-Whan Bae, MD, PhD (JACC: Asia)
Background: The Genoss paclitaxel-coated balloon (PCB) is a novel PCB with shellac and vitamin E as excipients, enhancing drug delivery to the target lesion and minimizing restenosis. Objectives: This study aimed to compare quantitative coronary angiographic outcomes at 6 months after treatment of de novo coronary artery disease (CAD) with 2 different types of PCBs. Methods: This prospective, multicenter, noninferiority trial randomized 204 patients with chronic coronary syndrome or stabilized acute coronary syndrome to treatment with the shellac and vitamin E-based PCB or the reference PCB (SeQuent Please NEO) in a 1:1 ratio. The primary endpoint was noninferiority for the 6-month angiographic in-lesion late lumen loss. Results: The 6-month in-lesion late lumen loss was 0.06 ± 0.38 mm with shellac and vitamin E-based PCB vs 0.09 ± 0.36 mm with reference PCB. The 1-sided 97.5% upper confidence limit of the difference was 0.08 mm, which was lower than the noninferiority limit of 0.15 mm, achieving noninferiority (P for noninferiority = 0.001). There was comparable late lumen enlargement (44.7% vs 42.7%; P = 0.903) and binary restenosis rates (3.2% vs 6.7%; P = 0.442) following treatment with shellac and vitamin E-based PCB and reference PCB, respectively. Both PCBs had similar 12-month rates of target vessel failure (3.0% in shellac and vitamin E-based PCB vs 4.3% in reference PCB; P = 0.921). Conclusions: The Genoss PCB, formulated with shellac and vitamin E as excipients, demonstrated angiographic outcomes comparable to a clinically proven PCB in the treatment of de novo CAD. (Compare the Safety and Efficacy of Genoss® DCB and SeQuent® Please NEO in Coronary De Novo Lesions; NCT05096442)